Effect of different technology combinations on upland rice production system - Santos, Alberto Baêta dos; Stone, Luis Fernando; Fageria, Nand Kumar; Prabhu, Anne Sitarama; Mah, Marcos Ga Ching; Aquino, Antonio Renes Lins de; Ajimura, Goes Matsutaro; Filho, Morel Pereira Barbosa; Zimmermann, Francisco José Pfeilsticker; Carvalho, José Ruy Porto de; Oliveira, Aldo Bezerra de; Filho, Austrelino Silveira (Pesquisa Agropecuaria Brasileira, 2014)
Six field experiments were conducted at the National Rice and Bean Research Center, Goiânia, with the objective of comparing the combined effect of the different practices recommended by research with those utilized by the rice farmers. The treatments included measures recommended to solve some of the principal problems that limit upland rice production. The use of supplementary irrigation significantly increased production, but its economic value needs further studies. Fertilizer application based on soil analysis resulted in higher yields when compared with fertilizer rates commonly used by farmers, even under drought conditions. Hand weed control was superior to the application of the herbicide Butachlor. Seed treatment did not consistently contribute to increased yield which should have occured as a consequence of the reduced incidence of pests and diseases. Cultivar IAC 47 was better adapted for upland conditions than the modern, semidwarf and high tillering cultivars. Better response to new technology was only obtained in years with normal rainfall distribution.
Keywords: supplementar irrigation; fertilization; weeding; herbicides; insect control; disease control; seed treatment; cultivars